Pendidikan Karakter Berbasis Budaya Lokal Tapis Lampung Sebagai Upaya Memperkuat Identitas Bangsa - Isbandiyah Isbandiyah; Supriyanto Supriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to analyze the values ​​of the character of Lampung Tapis as an effort to strengthen the identity of the Indonesian nation. The method used is a qualitative method with an ethnographic approach. The data collection technique uses library studies and the analysis model used is the Critical Discourse Analysis (CDA) model or critical discourse analysis. The results showed that Tapis fabric was made with a embroidery system, using cotton yarn and silver or gold thread and with decorative motifs of ingredients. Tapis cloth is usually worn by Lampung tribal girls and women, as supplies for traditional, religious and marriage ceremonies. In Tapis, the values ​​of life or character values ​​are developed in Lampung society. These character values ​​include sacred values, social stratification values, historical values ​​and understanding of nature, values ​​of creativity and inclusiveness, economic value, value of cooperation, and values ​​of perseverance, thoroughness and patience. Lampung Tapis cloth is one of the national identities of Indonesia which is not owned by other nations. Therefore, as an effort to strengthen the national identity, Lampung Tapis Fabrics were introduced to the international community. Based on the results of analysis from various sources, it can be concluded that Tapis is one form of achievement of Lampung society civilization Keywords: Character Value, Lampung Filter, National Identity